Portraying Son Preference Through Family Dynamics in Elif Shafak's Honour - Hilman Maulana Ibrahim; Adelie Grace Marianne litaay (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study examines the representation of son preference in Elif Shafak's novel Honour (2012), which traces three generations of a Turkish immigrant family across rural Turkey and London. "Son preference the systematic cultural valuing of sons over daughters remains deeply entrenched in Turkish and Kurdish patriarchal structures". The study addresses two research questions: how Shafak depicts son preference in the novel, and how son preference influences the experiences of female characters. A qualitative literary approach is applied through close reading of narratives, characters, and family dynamics, guided by two theoretical frameworks: Amartya Sen's (1990) son preference theory, which identifies the structural and cultural dimensions within which son preference operates, and Deniz Kandiyoti's (1988) concept of the patriarchal bargain, which explains how women navigate and reproduce patriarchal systems across generations. The findings reveal that Shafak depicts son preference through three interrelated dimensions of family life: parental behavior and reproductive choices, naming and symbolic treatment of children, and gender inequality in everyday family settings. Son preference affects the four main female characters in distinct ways: Naze accepts the patriarchal bargain completely at the cost of her life, Pembe perpetuates it while suffering under it, Esma recognizes inequality without being able to escape it, and Jamila rejects it but pays a genuine personal price. Together, these positions confirm that son preference in the novel operates not through external forces but from within the relationships that are supposed to protect women.